Influence of salinity on COD measurements in coastal water management. Issue 39 (20th August 2016) - Li, Zhaoran; Sheng, Yanqing; Shi, Wenjing; Sun, Qiyao; Mortimer, Robert J.G.
Abstract: Chemical oxygen demand (COD) is an important parameter in water quality assessment. COD values by different determination methods were investigated in coastal rivers. The results show that there is no clear relationship between CODCr and CODMn in coastal areas. CODCr does not reflect the degree of pollution of coastal waters. As salinity increased, CODCr and acidic CODMn increased significantly, but there was little/no change observed for alkaline CODMn . Coastal zone water quality standards should be proposed to solve connection problems between marine quality standard and surface water quality standard.